HISTORY ANALISIS KASUS PORTOFOLIO DENGAN METODE CAPITAL ASSET PRICING MODEL ATAS SAHAM INDUSTRI PERBANKAN DI PT. BES DENGAN PT BEI - Dewi Pujiani Kun Ismawati (Universitas Slamet Riyadi, 2015)
This research aims at: 1) in order to apply the concept of Capital Asset Pricing Model (CAPM) in the investment banking industry shares that go public in the company Surabaya Stock Exchange; 2) to find out which stocks can form optimal portfolio. Modern portfolio theory was first introduced formally by Dr. Harry M. Markowitz in the 1950s. Basically this portfolio theory is a theoretical framework for selecting the optimum portfolio-portfolio systematically. The literal sense is a set of portfolio investment opportunities. Methods used in this study is CAPM. As defined in the CAPM beta (β), so companies that have operating leverage is defined as a company that has high risk and the beta subunits. The main results in this study is there is a risk that the bank ' s shares as 0,733 with the expected profit rate of 3,45%; BNI had a level of risk with the level of profits that 0,309 expected 16,70%; Bank CIC International have risk-level profit 0,111 expected 6,40%; Bank Danamon has the risk level of profit 0,350 expected 19,33%; BII has the risk level of profit 0,454 expected 7,41%. The conclusion is a bank Danamon shares the least risk. Keywords: portfolio, CAPM, investment, risk, expected